Patches Approach to Investigate the Populational Dynamics in Dengue - Santos, F.l.p. (Sociedade Brasileira de Matemática Aplicada e Computacional, 2017)
ABSTRACT In areas where resources are located in patches or discrete locations, human dispersal is more conveniently modeled, in which the population is divided into discrete patches. In this work we develop a general discrete model to analyze the spread of Dengue disease. In the process of mathematical modeling we take into account the human populations and the circulation of a single serotype of dengue mosquitoes. The movements of susceptible, infected and recovered humans among all patches are considered. Aquatic phases with different carrying capacities are considered within the patches. Also an arbitrary number of patches can be used to simulate the spread of dengue disease. In this paper we performed numericalexperiments to show the applicability of this methodology to investigate the dengue disease problem. The general discrete space model was developed for solving epidemiological problems whereas the human-vector interactions and human mobilities play an important role. Based on our numerical results, we may recommend the general patches model for solving epidemiological problems in Population Dynamics.

RESUMO Em áreas onde os recursos estão localizados em locais discretos, a dispersão humana é mais convenientemente modelada considerando a população dividida em regiões discretas (patches). Neste trabalho, desenvolvemos um modelo espaço discreto geral para analisar a propagação da doença da dengue. No processo de modelagem matemática, levamos em consideração as populações humanas e a circulação de um único sorotipo de mosquitos da dengue. A mobilidade dos seres humanos suscetíveis, infectados e recuperados entretodos os patches é considerada. As fases aquáticas com distintas capacidades de suporte são consideradas dentro de cada patch. Além disso, um número arbitrário de patches podem ser usados para simular a propagação da doença da dengue. Este modelo espacialmente discreto foi desenvolvido para resolver problemas epidemiológicos, em que interações homem-vetor e a mobilidade humana desempenham um papel importante. Com base nos resultados numéricos obtidos, podemos recomendar o modelo em patches para a resolução de problemas epidemiológicos em Dinâmica Populacional.
Keywords: human dispersal; discrete space model; pathway approach; system of ODEs; Euler method; population dynamics; Dispersão humana; modelo espaço discreto; abordagem pathway; sistema de EDO’s; método de Euler; dinâmica populacional